Probing the Fermi surface by positron annihilation and Compton scattering - Dugdale, S.B. (Физика низких температур, 2014)
Positron annihilation and Compton scattering are important probes of the Fermi surface. Relying on conservation
of energy and momentum, being bulk sensitive and not limited by short electronic mean-free-paths, they can
provide unique information in circumstances when other methods fail. Using a variety of examples, their contribution
to knowledge about the electronic structure of a wide range of materials is demonstrated.